1977
DOI: 10.1111/j.1151-2916.1977.tb14088.x
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of Monoclinic Hafnium Oxide at Room Temperature

Abstract: The Young's and shear moduli of polycrystalline monoclinic hafnium oxide were determined by the sonic resonance method at room temperature as a function of volume fraction porosity. The Spriggs equation empirically described the data and the zero porosity moduli as 283.6 GN/mZ and 109.2 GN/m2 for Young's and shear moduli, respectively. The Debye temperature calculated from the elastic constants was 484°K. Several specimens had anomalously low moduli values, attributed to microcracking. Grain size and internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…However, it is close to the range of 200-250 GPa reported by Wang for dense poly-crystalline HfO 2 ceramics of varying purity and microstructure. 144 These observations are consistent with both the ALD HfO 2 film exhibiting a nano-crystalline monoclinic structure in XRD and the NRA-RBS mass density being only slightly reduced relative to the theoretical single-crystal density (10.1 g/cm 3 ) 250 and nearly Thk. = thickness, Y.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…However, it is close to the range of 200-250 GPa reported by Wang for dense poly-crystalline HfO 2 ceramics of varying purity and microstructure. 144 These observations are consistent with both the ALD HfO 2 film exhibiting a nano-crystalline monoclinic structure in XRD and the NRA-RBS mass density being only slightly reduced relative to the theoretical single-crystal density (10.1 g/cm 3 ) 250 and nearly Thk. = thickness, Y.…”
supporting
confidence: 73%
“…With respect to the hardness of the PEALD AlN, the value of 22 ± 4 GPa determined in this study is significantly higher than the value of 17 GPa reported for a single-crystal AlN substrate, 245 but consistent with the value of 22 GPa previously reported for a sputter-deposited poly-crystalline AlN thin film. 247 The nanoindentation Young's modulus of 177 ± 5 GPa for the ALD HfO 2 film is also substantially reduced relative to the theoretical value of 300 GPa determined for single-crystalline monoclinic HfO 2 in the DFT calculations of Wu, 249 and the value of 283.6 GPa reported by Dole 250 for unstabilized poly-crystalline monoclinic HfO 2 . However, it is close to the range of 200-250 GPa reported by Wang for dense poly-crystalline HfO 2 ceramics of varying purity and microstructure.…”
mentioning
confidence: 79%
“…Status Solidi B 248, No. 4 (2011) 953 Table 2 The calculated results of elastic constants, the bulk, shear and Young modulus, Poisson coefficient, the shear, compressional and average sound velocity, Debye temperature and B X /G X at the applied pressure, and the theoretical [13,14] and experimental [23] values at 0 GPa are presented.…”
Section: Effective Massesmentioning
confidence: 99%
“…Table 2 shows the elastic constant values at the applied pressure. For the sake of comparison, the theoretical [13,14] and experimental [23] values at 0 GPa are presented. The agreement with previous results is excellent.…”
Section: Effective Massesmentioning
confidence: 99%
See 1 more Smart Citation